Pengaruh Breathing Exercise Terhadap Level Fatigue Pasien Hemodialisis - Djunizar Djamaludin; Rini Safriany; Rika Yulenda Sari (Universitas Malahayati Lampung, 2021)
ABSTRACT: THE EFFECT OF BREATHING EXERCISE ON FATIGUE LEVELS OF HEMODIALISTIC PATIENTS Introduction: Fatigue is one of the problems with a high prevalence among the effects of hemodialysis on patients with late stage kidney disease. Breathing exercise is a non-pharmacological therapy to deal with various complaints such as fatigue. Abdul Moloek Hospital in Lampung Province is one of the largest referral hospitals for hemodialysis therapy for patients with chronic kidney failure. The number of kidney failure patients in 2018 is 220 patients.Objective: the effect of Breathing Exercise on the Fatigue Level of Hemodialysis Patients in Dr. Hi Abdul Moeloek Hospital in Lampung Province in 2019.Method: Quantitative research type, using a quasi-experimental approach. The study population was patients with kidney failure who underwent hemodialysis in February 2019 at Dr Hi Abdul Moeloek Hospital in Lampung Province as many as 300 people. The sample uses a purposive sampling of 30 respondents. Data collection techniques was done by observation. The statistical test used is the dependent t test.Results: The frequency distribution of respondents aged ≥ 50 years was 22 (73.3%), male sex was 19 (63.3%) and had a junior high school education of 10 (33.3%). The average level of fatigue of hemodialysis patients before Breathing Exercise was 37.23, after Breathing Exercise was 33.1.Conclusion: There was the effect of breathing exercise on the level of fatigue of hemodialysis patients (p value 0,000). Breathingexercise is a nursing intervention that can be done to overcome weaknesses. Continuous exercise can improve health, so that the quality of life of hemodialysis patients will improve. Keywords: Breathing Exercise, Fatigue, Hemodialysis INTISARI : PENGARUH BREATHING EXERCISE TERHADAP LEVEL FATIGUE PASIEN HEMODIALISIS Pendahuluan: Fatigue atau kelelahan adalah salah satu masalah dengan prevalensi yang cukup tinggi diantara efek tindakan hemodialisis yang diterima pasien dengan penyakit ginjal tahap akhir. Breathing exercise adalah terapi nonfarmakologi untuk mengatasi berbagai keluhan seperti fatigue. RSUD Abdul Moloek provinsi lampung merupakan salah satu rumah sakit rujukan terbesar untuk melakukan terapi hemodialisis bagi pasien gagal ginjal kronis. Jumlah pasien gagal ginjal tahun 2018 sebanyak 220 pasien.Tujuan: diketahui pengaruh Breathing Exercise Terhadap Level Fatigue Pasien Hemodialisis Di RSUD Dr Hi Abdul Moeloek Provinsi Lampung Tahun 2019.Metode: Jenis penelitian kuantitatif, menggunakan pendekatan quasi eksperimen. Populasi penelitian adalah penderita gagal ginjal yang menjalani hemodialisa pada bulan Februari 2019 sejumlah 300 orang. Sampel menggunkan purposive sampling sejumlah 30 responden. Tehnik pengumpulan data dilakukan dengan observasi. Uji statistik yang digunakan adalah uji t dependen. Hasil: distribusi frekuensi responden berusia ≥ 50 tahun (73,3%), berjenis kelamin laki-laki (63,3%) dan berpendidikan akhir SMP (33,3%). Rata-rata Level Fatigue sebelum diberikan Breathing Exercise adalah 37.23. Sesudah diberikan Breathing Exercise adalah 33.1.Kesimpulan: Ada pengaruh breathing exercise terhadap level fatigue pasien hemodialisis (p value 0,000). Breathingexercise merupakan intervensi keperawatan yang dapat dilakukan untuk mengatasi kelemahan. Latihan yang kontinyu dapat meningkatkan kesehatan, sehingga kualitas hidup pasien hemodialisis akan meningkat. Kata Kunci : Breathing Exercise, Fatigue, Hemodialisis